Implementasi Pembelajaran Berdiferensiasi pada Mata Pelajaran Bahasa Indonesia di Kelas X UPT SMAN 1 Pinrang - Dollah, Alfina Ali; Sultan, Sultan; Haliq, Abdul (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to examine the implementation of differentiated learning in Indonesian subjects in class X UPT SMAN 1 Pinrang, South Sulawesi. The specific purpose of this research is to know, analyze, and describe the implementation of differentiated learning from the aspects of content, process, and products in Indonesian subjects. This research uses a qualitative approach with a descriptive design. Data was obtained through interviews with two Indonesian teachers in class X, observation of learning in class, and analysis of learning tool documents. Data analysis follows the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of content-differentiated learning is carried out by adjusting students' learning styles and learning media used in the classroom. Process differentiation is applied through project-based learning methods, class discussions, and lectures. Student-generated products include scrapbooks, powerpoints, posters, and hands-on practice. This study concludes that the implementation of differentiated learning in class X UPT SMAN 1 Pinrang has succeeded in creating an effective and meaningful learning experience for students.